Design and development of Web-Based Information System for The Batik Industry - Soesanti, Indah (Institut Teknologi Sepuluh Nopember, 2014)
An Information systemÂ is any combination ofÂ information technologyÂ and people's activities using that technology to support operations, management, and decision-making. Some industries need web-based information system. Information system for the batik industry is designed to process data such as text, image, and produce information. The planning of web-based information systems needs a proactive review of the capabilities of the Internet technology to serve the particular needs of the firm and its customers. Process steps for designing the batik industry information system are software architecture, algorithm, data structure, and interface representations. The results show that the web-based information system that designed in this research is implemented successfully.